The golden egg [large type] - Leon, Donna (Leon, Donna. Commissario Guido Brunetti mystery., 2013)
As the first leaves of autumn begin to fall, Vice Questore Patta asks Commissario Guido Brunetti to look into a minor violation committed by the mayor's future daughter-in-law. Brunetti has no interest in helping his boss amass political favors, but has little choice but to comply. Then the sweet, simple-minded man who worked at the dry cleaner dies of a sleeping pill overdose, and Brunetti's wife, Paola, asks him to investigate. But why would anyone want him dead? (Bestseller)